Probiotics for Children With Recurrent Abdominal Pain - Ahmad Rizal, Ahmad Rizal; Indra Wijaya, Indra Wijaya (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the use of probiotics for children with recurrent abdominal pain (RAP) has revealed a complex interplay of potential benefits and significant gaps in research. Initial studies, such as that by (Gordon et al., 2017), identified a limited number of trials and called for clearer outcome measures, highlighting the necessity for well-defined metrics such as pain severity and psychosocial impacts. This foundational work set the stage for a deeper exploration of probiotics' role in managing functional abdominal pain disorders among children aged 4 to 18. Literature Review: Subsequent reviews, including that by (Abbott et al., 2018), emphasized the multifactorial nature of RAP, suggesting that various psychological and physical triggers may contribute to this condition. In examining specific probiotic strains, (Hojsak et al., 2018) acknowledged the potential benefits of Lactobacillus rhamnosus GG (LGG) and Lactobacillus reuteri DSM 17938, yet highlighted the absence of comprehensive guidelines for their clinical application. Further exploration by (Capozza et al., 2022) reiterated the necessity for caution, indicating that while certain probiotics may offer therapeutic benefits, the current evidence does not support their routine use for prevention. Conclusion: In conclusion, while there is accumulating evidence supporting the efficacy of certain probiotic strains in managing recurrent abdominal pain in children, the literature also reveals substantial gaps that must be addressed. Future research should focus on conducting larger, well-designed trials that explore optimal strains, dosages, and long-term effects. Establishing clear guidelines and treatment protocols will be essential for integrating probiotics into clinical practice effectively.